3D core-shell structured NiFe layered double hydroxide with NiCo2O4 as an efficient electrocatalysts for oxygen evolution reaction. (July 2022) - Wang, Shenggao; Li, Jiahao; Fang, Han; Li, Boyang; Wang, Geming; Gao, Yuan
Abstract: In this work, a 3D core-shell NiFe-LDH/NiCo2 O4 /NF nanostructured composite with intimate interface have been successfully synthesized via a two-step hydrothermal approach. The core-shell composites demonstrate excellent electrocatalytic behavior due to its unique 3D core-shell microstructure and the optimized electron migration pathway. When NiFe-LDH anchors on the surface of NiCo2 O4, the formation of Fe 3+, Ni 3+ and Co 2+ in the composite induced by electrons migrate from Fe 2+ and Ni 2+ in the NiFe-LDH shell to Co 3+ in the NiCo2 O4 core can significantly promote charge transfer across interface and thereby boosting its oxygen evolution reaction (OER). In comparison to its single-component and hydroxide, the composite delivers a low overpotential of 363 mV for 50 mA cm −2, a small Tafel slope of 53.03 mV·dec −1, and satisfactory long-term stability, which makes it comparable to commercial IrO2 catalysts. These results show on how 3D core-shell architecture and valence states of metal oxides influence on OER performance in NiFe-LDH/NiCo2 O4 electrocatalysts and provide new insights for regulating LDH-based electrocatalysts. Highlights: The 3D core-shell NiFe-LDH/NiCo2 O4 /NF nanostructured composite with intimate interface has been successfully synthesized. The NiFe-LDH/NiCo2 O4 /NF electrocatalyst show outstanding OER activity. Their outstanding OER can be attributed to 3D core-shell nanostructure and optimized electron migration pathway. The electrons transfer between NiFe-LDH shell and NiCo2 O4 core lead to high content of Fe 3+, Ni 3+ and Co 2+ in composite.